NAIRU estimates for Germany: New evidence on the inflation-unemployment trade-off - Florian Kajuth (Deutsche Bundesbank, 2010)
The paper estimates the NAIRU from a Phillips curve relationship in the state-space framework. To identify the inflation-unemployment trade-off we account for a time-varying inflation trend to control for the part of inflation that is not affected by the cyclical component of unemployment. In addition we use shifts in the relative volatility of shocks to unemployment and inflation to address the simultaneity problem in Phillips curve estimations. Applying the method of Rigobon and Sack (2003) allows for a data driven identification of the contemporaneous coefficients on the unemployment gap in the Phillips curve and yields more precise estimates of the structural coefficients in the Phillips curve. This tightens the economic relation on the basis of which the NAIRU is derived.
Keywords: E24; E31; E32; 330; non-accelerating inflation rate of unemployment; state-space estimation; identification through heteroskedasticity; trend inflation; Natürliche Arbeitslosigkeit; Phillips-Kurve; Zustandsraummodell; Heteroskedastizität; Schätzung; Deutschland